2019
DOI: 10.1002/aelm.201800860
|View full text |Cite
|
Sign up to set email alerts
|

Band Structure and Spin–Orbital Texture of the (111)‐KTaO3 2D Electron Gas

Abstract: metal-insulator transitions, among others. It is this plethora of bulk properties that enrich the phase diagrams of transition metal oxides compared to those of conventional semiconductors, and which renders 2DEGs in correlated materials so promising for the discovery of new functionalities and emergent physical phenomena. This is exemplified by the observation of superconductivity, [3] magnetism, [4] strong electron lattice interactions, [5] and quasi 1D conductivity [6] in the 2DEG stabilized in (001)-orient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 47 publications
5
74
0
2
Order By: Relevance
“…S4 [18]). Considering that the existence of striking asymmetric twofold oscillations in magnetoresistance manifests deep inside the superconducting region and vanishes in the normal state, we can straightforwardly rule out the possibilities of ex- trinsic contributions, such as the magnetic field induced Lorentz force effect [34] and the electronic band structure inherent to the KTaO 3 with respect to the underlying threefold lattice symmetry [35] [also see Fig. 1(c)], and thus demonstrate that this anisotropy is an intrinsic property of the superconducting phase in YAlO 3 /KTaO 3 .…”
Section: (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…S4 [18]). Considering that the existence of striking asymmetric twofold oscillations in magnetoresistance manifests deep inside the superconducting region and vanishes in the normal state, we can straightforwardly rule out the possibilities of ex- trinsic contributions, such as the magnetic field induced Lorentz force effect [34] and the electronic band structure inherent to the KTaO 3 with respect to the underlying threefold lattice symmetry [35] [also see Fig. 1(c)], and thus demonstrate that this anisotropy is an intrinsic property of the superconducting phase in YAlO 3 /KTaO 3 .…”
Section: (D)mentioning
confidence: 99%
“…In the YAlO 3 /KTaO 3 the lack of inversion symmetry, however, tends to mix spin-singlet and spin-triplet driven by strong spin-orbit coupling [39]. Indeed, the conducting electrons with strong spin-orbit coupling originating from the heavy Ta 5d orbitals has been revealed at KTaO 3 interfaces [35,40]. Due to the absence of a mirror plane parallel to the interface of YAlO 3 /KTaO 3 , the point group of YAlO 3 /KTaO 3 is C 3v , which does not contain the symmetry element of an inversion.…”
Section: (D)mentioning
confidence: 99%
“…surf . Consistent with the need to screen the associated polar discontinuities, the surfaces readily form two-dimensional electron gases that have been well characterized using angle-resolved photoemission [26,27,28]. (Note that an interface of KTaO 3 is electrostatically similar to a surface, provided that its neighbor is not a coherent I-V perovskite oxide, and so we use the term surface also for interfaces with systems that are not the vacuum).…”
Section: Discussionmentioning
confidence: 99%
“…53 BaTiO 3 can be then expected to have a comparable λ. Perovskites consisting of heavier elements, such as LiOsO 3 or KTaO 3 (KTO), are expected to have stronger SOC, and hence stronger λ. Indeed, for KTO the SOC-related splitting in the band structure of around 400 meV 54,55 , an order of magnitude larger than in STO. For LiOsO 3 it has been reported that, unlike other 5d transition-metal oxides, the effect of SOC on the band structure is small 56 .…”
Section: Experimental Proposalmentioning
confidence: 95%